Minat Siswa SMA Negeri di Kabupaten Kulonprogo terhadap Kegiatan Ekstrakulikuler Olahraga - Tri Subekti (Jurnal Pendidikan Jasmani Indonesia, 2005)
This research aims to find out how much interest of students of Senior HighSchool to sport extracurricular activity in state schools at Kulonprogo regency.Population of this research are students of State Senior High School at Kulonprogoregency. Sampling population is 320 students obtained by random complete sequence.Method used in this research is by survey and data collecting technique using questionnaire.Result of this research shows that interest to sport extracurricular activity is 74% (quiteinterested). Factors in interest show percentage rate: contentment of 77% and obstruction of 69%. The most interested sport extracurricular is volley ball and then followedby other sports like basket ball, badminton, and soccer.Keywords: Interest, Extracurricular